ASPEK SOSIAL EKONOMI KERAGAMAN HAYATI - I GUSTI AYU AGUNG LIES ANGGRENI (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2000)
People wherever they are living, are influenced by biotic and abiotic factors. Totalof living organisms from single cell organism such as bacteria to higher level organisms suchas various plants and animals is known as biological diversity or biodiversity. Biodiversitygives opportunities to people to develop their knowledge and technologies to utilizebiodiversity for their daily lives such as food, medicines, industrial goods and housing. Thus,many aspects of people lives are directly or indirectly influenced by biodiversity.